Pemberdayaan Petambak Garam melalui Program Pemberdayaan Usaha Garam Rakyat (PUGAR) di Kabupaten Brebes Tahun 2011-2014 - Wardiansyah Wardiansyah; Wiwik Widayati; Ahmad Taufiq (Journal of Politic and Government Studies, 2015)
Abstract The wood craft industry is one of business that has a big contribution in Jepara’s economy. The wood craft industry GDP’s value higher than others make this industry has been choosen by majority of Jepara people. Moreover, because so strong products created on the national of international scene, Jepera City has a nickname “Carving Center”. In this case, researcher would try to investigate what is the role of Jepera’s Local Goverment in Keeping the continuity and existance of wood craft industry in “Carvung Center”.The goal of this research is to know the roles performed by Jepara local goverment in keeping continuance and the existance of wood craft industry. This research is a type of qualitative research. Than type of research used in this research is descriptive analytic research. The data capture through interviews and and Departement of Industry and Comerce Jepara’s documents.Based on research result, it is known that the role of Jepara’s local goverment in keeping the existance of wood craft industry divided into 3 funtions, those are as regulatory policies, facilitatory, and motivator. As regulatory policies, the local goverment has published Perda No. 17 year 2013 about industry potection. Then as facilitators, the local goverment often has contribution to advance the wood craft industry enterprises. One of which is increas the quality of Human Resources. The activities of the local goverment in order to improve the quality of human resources are training, aid equipment and apprenticeship for craftsmen and entrepreneurs. Then, the last is motivator for wood craft industry, the local goverment has built cooperative relationship with institutions that take care of the wood craft industry.Research that has been done to provide information that in keeping the existance of wood craft industry in Jepara, local goverment have contribute and carry out takes according to their working area. But, one thing that needs to be underline that is basically the wood craft industry needs regulations that give special attention to wood craft industry. Because with the rules that focus in wood craft industry can walk up. Therefore, when there issue and problems that arise and threaten the survival of the wood craft industry in Jepara can be overcame well. Keywords: the role of goverment, wood craft industry